Masculinity, patronage politics, and the feminization of school spirit in the Ateneo-Las Salle UAAP rivalry - Lizada, Miguel Antonio N. (2015)
This paper looks at the feudal structure of the collegiate sports industry, specifically the Ateneo-La Salle rivalry of the University Athletics Association of the Philippines (UAAP). I begin by looking at how basketball rivalry through its modes of fan consumption (cheering, branding, media reports, the internet and other interfaces) is constructed for a male gaze. Such a gaze is part of a larger narrative that replicates patronage politics. Both schools enjoy patronage in terms of acquiring equipment and players (regarded by media as "mercenaries") from two wealthy businessmen: Manuel V. Pangilinan for Ateneo and Eduardo Cojuangco Jr. for La Salle. Collegiate basketball is utilized as a meaningful text that affirms the power relations of contemporary feudal politics and school spirit is seen here as a mode of channeling fraternal energies to sustain such relations. I analyze women's volleyball next and how it functions as a counterpoint as the fan culture originated from and is sustained by "outsiders". I will discuss how this elastic fan culture (the attendance of "outsider fans", the proliferation of "fake" merchandise produced by informal economies, and the rise of independent fan groups), existing beyond the mechanics set by mainstream industries cumulatively feminize the school spirit industry. My analysis of volleyball fan culture ends with a reflection on the possibility that such potentially subversive modes of fan consumption may in fact be co-opted by the dominant structures of industry. I conclude my paper by arguing how regardless of the possibility of co-optation, the Ateneo-La Salle rivalry in its current state reveals the malleable relationship between material conditions and commodity, and how power dynamics of a commercialized industry may in fact be reconstituted to open new and exciting possibilities for counterhege.
Keywords: Ateneo de Manila University; De La Salle University; Sports participation; Consumer behavior